Menghidupkan semula pedagogi inkuiri falsafah di kalangan pendidik dan pelajar Islam - Hashim, Rosnani (Yayasan Takmir, 2009)
Muslims and Muslim societies are more frequently challenged today by many internal and external threats. Externally they are threatened with globalization, modernity, non-Islamic cultures and values particularly from the West, post-modernity and liberalism and recently to all kinds of Islamophobia. Internally, they are suffering from a crisis of values as a result of this onslaught - ranging from gender issues to human rights and democracy. Information and communication technologies seem to accelerate the pace ofthese threats. How can the Muslim minds withstand this intellectual and ideological onslaught? How should their education system, curriculum and educators respond? The purpose ofpaper is to dissect the problem andarguesfor a different pedagogical approach in the education ofMuslim youth. Their education should empower and motivate them so that they can determine the direction of their lives rather than beingfed with 'education' that is not meaningful to them. It is to inform educators that they should incorporate the pedagogy ofphilosophical inquiry as the necessary tool to awaken the Muslim minds.